POTENSI BIOMASSA, KARBON DAN SERAPAN KARBONDIOKSIDA TUMBUHAN BAWAH DI HUTAN RAWA GAMBUT PROVINSI KALIMANTAN TENGAH: Potency of Biomass, Carbon and Carbondioxide Absorption Understorey in Peat Swamp Forest, Central Kalimantan Province - Ajun Junaedi; Christopheros; Moh Rizal; Tioliliani Lubis (HUTAN TROPIKA, 2020)
This study aims to identify the species composition and estimate the potency for biomass, carbon and carbondioxide (CO2) uptake of understorey at a peat depth of 1 - <2 m; 2 - <4 m; 4 - <8 m and 8 - <12 m in Sebangau National Park Central Kalimantan. The results showed that the total number of understorey species found in all peat depths was 21 species. The most common understorey species found were at peat depths of 4 - <8 m, with 13 species. Several understorey species that dominate the entire peat depth are Pandanus tectorius, Pandanus amaryllofolius and Stenochlaena palustris. The potency of understorey biomass, carbon storage and CO2 absorption in all peat depths ranged from: 1.73 to 2.71 tons/ha; 0.81 - 1.30 tonC/ha and 2.98 - 4.77 tonsCO2/ha. Understorey that grows at a peat depth of 4 - <8 m has the highest potency for biomass, carbon and CO2 absorption.Keywords: biomass, carbon, carbondioxide, peat swamp forest, understorey